THE DIFFERENT EFFECTS OF ZINC SUPPLEMENT AND VELVET BEAN MUCUNA PRURIENS EXTRACTS TOWARD FERTILITY OF BALBC/ MICE - Kurniasanti, Pradipta Pradipta; Rahfiludin, M Zen; Winarni, Sri (Jurnal Ilmu Kesehatan dan Kesehatan, 2018)
Abstract: Good quality velvet beans and zinc supplement are well studied and known as rich source ofaphrodisiac. The following reseach was carried out to study the difference effect of zinc supplement (ZS)and velvet bean extracts (VBE) towards fertility of BALB/c mice i.e the number of sperm, the motility ofsperm, the viability of sperm, the morphology of sperm, the existence of vagina plug, and the birthcondition of mice. This study was an experiment using Posttest Only Controlled Group Design with threegroups. The first group (A1) as control, the second group (A2) receives subcutaneous injection of 2-methoxyethanol fraction as much as 200 mg/kg weight/day for 5 days, followed with ZS at a dosage of0,026 mg/day/head, and the third group (A3) receives subcutaneous injection of 2-methoxyethanolfraction as much as 200 mg/kg weight/day for 5 days, followed with VBE at a dosage of 56 mg/kg weight/day for 30 days. The quality of spermatozoa of A1, A2, and A3 was significant difference (p < 0.05).Both of A2 and A3 were no significant difference of mean number of sperm (p = 0.274), mean percentageof sperm motility (p = 0.739), mean percentage of sperm viability (p = 0.141) and mean value ofmorphology of sperm (p = 0.394). The quality of spermatozoa and the total number of baby mice livedand died of A1, A2 and A3 were significant difference. In addition, there was no significant differencein the existence of female mice's vaginal plug of A1, A2 and A3. This study showed that ZS and VBE canincrease the quality of spermatozoa of BALB/C mice.